Chromatin remodelling factor BAF155 protects hepatitis B virus X protein (HBx) from ubiquitin-independent proteasomal degradation - Huijing Chen; Yi Zhang; Shuangshuang Ye; Qiong Wu; Youfen Lin; Kaiqin Sheng; Wannan Chen; Xinjian Lin; Xu Lin (Emerging Microbes and Infections)
HBx is a short-lived protein whose rapid turnover is mainly regulated by ubiquitin-dependent proteasomal degradation pathways. Our prior work identified BAF155 to be one of the HBx binding partners. Since BAF155 has been shown to stabilize other members of the SWI/SNF chromatin remodelling complex by attenuating their proteasomal degradation, we proposed that BAF155 might also contribute to stabilizing HBx protein in a proteasome-dependent manner. Here we report that BAF155 protected hepatitis B virus X protein (HBx) from ubiquitin-independent proteasomal degradation by competing with the 20S proteasome subunit PSMA7 to bind to HBx. BAF155 was found to directly interact with HBx via binding of its SANT domain to the HBx region between amino acid residues 81 and 120. Expression of either full-length BAF155 or SANT domain increased HBx protein levels whereas siRNA-mediated knockdown of endogenous BAF155 reduced HBx protein levels. Increased HBx stability and steady-state level by BAF155 were attributable to inhibition of ubiquitin-independent and PSMA7-mediated protein degradation. Consequently, overexpression of BAF155 enhanced the transcriptional transactivation function of HBx, activated protooncogene expression and inhibited hepatoma cell clonogenicity. These results suggest that BAF155 plays important roles in ubiquitin-independent degradation of HBx, which may be related to the pathogenesis and carcinogenesis of HBV-associated HCC.